Blended Learning Model in a Distance Learning System to Increase 4C Competence (Creativity, Critical Thinking, Collaboration, and Communication) - Vera Septi Andrini; Andista Candra Yusro (Universitas Negeri Makassar, 2021)
The purpose of this study is to develop a learning model based on Blended Learning in the concept of Distance Learning in order to be able to improve students' 4C competencies. The research conducted is a type of research quasi-experimental (quasi-experimental). Research instruments include: questionnaires, observation guidelines, validation sheets, FGD instruments, tests, and documentation. The research subjects involved 57 sudents in second semester who were taking Basic Natural Sciences courses. The model trial used a one group pretest-posttest design. Test the effectiveness of the developed model using the t test. Improvement of 4C Skills Competence using the Gain Score test. The results showed that there was an effect of the blended learning model in the distance learning system on increasing 4C competencies (Creativity, Critical Thinking, Collaboration, and Communication). The N-Gain test is 0.6 (medium category) which means that there is an increase in 4C competence before and after being given the blended learning model. The data shows that the average value for the pretest results is 63.14 and the average posttest score is 82.65. The novelty of this research is the application of various online platforms such as Google Classroom, Google Slides, Google Meet, Kahoot, online educandy games, and youtube in supporting the blended learning model.